Lyra2: Password Hashing Scheme with improved security against time-memory trade-offs - Andrade, Ewerton R.; Simplicio Junior, Marcos A. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2017: Anais do XXX Concurso de Teses e Dissertações, 2017)
To protect against brute force attacks, modern password-based authentication systems usually employ mechanisms known as Password Hashing Schemes (PHS). Basically, a PHS is a cryptographic algorithm that generates a sequence of pseudorandom bits from a user-defined password, allowing the user to configure the computational costs involved in the process aiming to raise the costs of attackers testing multiple passwords trying to guess the correct one. In this context, the goal of this research effort is to propose a novel and superior PHS alternative. Specifically, the objective is to improve the Lyra algorithm, a PHS built upon cryptographic sponges whose project counted with the authors' participation. The resulting solution, called Lyra2, preserves the efficiency and flexibility of Lyra, and it brings important improvements when compared to its predecessor: (1) it allows a higher security level against attack venues involving time-memory trade-offs; (2) it includes tweaks for increasing the costs involved in the construction of dedicated hardware to attack; (3) it balances resistance against side-channel threats and attacks relying on cheaper (and, hence, slower) storage devices. Besides describing the algorithm's design rationale in detail, the thesis also includes a detailed analysis of its security and performance.